To solve this problem, we will simplify the expression using the properties of operations and rules for multiplying and dividing.
First, we can simplify the division of (-3) by (3/4):
(-3) ÷ (3/4) = (-3) × (4/3) = -12/3 = -4
Next, we can multiply the result by (2/7):
-4 × (2/7) = (-4/1) × (2/7) = (-4 × 2) / (1 × 7) = -8/7
After that, we can multiply the result by (- 5/26):
-8/7 × (- 5/26) = (-8/7) × (5/26) = (-8 × 5) / (7 × 26) = -40/182 = -20/91
Finally, we divide the result by (5/7):
-20/91 ÷ (5/7) = (-20/91) × (7/5) = (-20 × 7) / (91 × 5) = -140/455 = -28/91
Therefore, the solution is -28/91.
Use the properties of operations and rules for multiplying and dividing to solve
(-3)÷(3/4)×(2/7)×(- 5/26)÷(5/7)
1 answer